Mid-term to long-term results of primary arthroscopic Bankart repair for traumatic anterior shoulder instability: a retrospective study - Panzram, Benjamin; Kentar, Yasser; Maier, Michael Wolfgang; Bruckner, Thomas; Hetto, Pit; Zeifang, Felix (BMC musculoskeletal disorders, 2020)
The arthroscopic method offers a less invasive technique of Bankart repair for traumatic anterior shoulder instability. The aim of the study is to determine the mid−/long-term functional outcome, failure rates and predictors of failure after primary arthroscopic Bankart repair for traumatic anterior shoulder instability.
Gesehen am 20.04.2020